Covid 19 guided second-generation economic reforms - Dr. R K Arya, Dr. Swati Watts, Dr. Arvind Dalal (International Journal of Advanced Science and Technology, 2020)
India was known to suffer from disguised unemployment in agriculture but no doubt this is not the issue at this stage but the return from the farming in 80 percent of the farms are below average. As the growth of big industries was considered for making foreign exchange reserve as much as possible the government had not taken any major step to create technical base within the country China was nowhere in the textile when India was the sole producer of textile goods but in the present situation Bangladesh and Vietnam are taking over the textile business from China and India is just watching how come it is not possible. There are clear well-founded reasons. While India had confronted with Balance of Payment situation in 1991, it had one major problem to face i.e payment of oil and for the payment of which it was running short of foreign exchange. While broadly the reform was known with LPG i.e liberalization, globalization, and privatization but largely it was to attract foreign investment and allow private investment to take place as much as possible. In the last two decades, India has disowned many public sectors or offloaded the equity from them but it is the large private industries that grabbed the opportunity in some cases well-developed township had to be surrendered. Such was the situation. The reason is that each government was expected to first think of the external environment i.e maintaining exchange rate and getting capital as much as possible, the healthy public sector units had to be surrendered for pecuniary gains.